Study of Green Roof System Implementation in Green Building Construction - Vooi Teng, Tan; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2021)
The green roof system is an extension of the existing roof, which involves a minimum, high-quality waterproofing, root repellent system, drainage system, filter cloth, a lightweight growing medium, and plants. The major issue that affecting the implementation of the green roof system is achieve a cost disadvantage since it includes a huge cost of implementation. In Malaysia, the green roof system is still considered a new concept that can offer many benefits. Therefore, the purpose of this study is to identify the types, benefits and problems of the green roof system implementation. The G7 level contractor in Malaysia will be the target respondent in this research and the qualitative method will be using which is conducting a virtual interview. The data have been obtaining from the interview section and the thematic analysis method has been using to analyze the collected data. By conducting this research, it can be identified the types, benefits and problems of the green roof system implementation in green building construction. In conclusion, it will have a clear understanding about the types of the green roof system, which is a semi-intensive green roof system, intensive green roof system, and extensive green roof system. Furthermore, the benefits of the implementation of the green roof system, which is stormwater management, enhance biodiversity, and reduces greenhouse gases. Finally, the implementation of the green roof system requires a huge cost, complicated design, inexperienced contractor and maintenance and operation work.